Immunobiology and pathogenesis of hepatitis B virus infection - Iannacone, Matteo; Guidotti, Luca G (Nature reviews. Immunology, 2022)
Hepatitis B virus (HBV) is a non-cytopathic, hepatotropic virus with the potential to cause a persistent infection, ultimately leading to cirrhosis and hepatocellular carcinoma. Over the past four decades, the basic principles of HBV gene expression and replication as well as the viral and host determinants governing infection outcome have been largely uncovered. Whereas HBV appears to induce little or no innate immune activation, the adaptive immune response mediates both viral clearance as well as liver disease. Here, we review our current knowledge on the immunobiology and pathogenesis of HBV infection, focusing in particular on the role of CD8 T cells and on several recent breakthroughs that challenge current dogmas. For example, we now trust that HBV integration into the host genome often serves as a relevant source of hepatitis B surface antigen (HBsAg) expression during chronic infection, possibly triggering dysfunctional T cell responses and favouring detrimental immunopathology. Further, the unique haemodynamics and anatomy of the liver - and the changes they frequently endure during disease progression to liver fibrosis and cirrhosis - profoundly influence T cell priming, differentiation and function. We also discuss why therapeutic approaches that limit the intrahepatic inflammatory processes triggered by HBV-specific T cells might be surprisingly beneficial for patients with chronic infection.